Desenvolvimento e validação de instrumento para avaliação da integração ensino-serviço-comunidade nos cursos de graduação em Odontologia - Toscano, Raíssa Lima (2022)
Introduction: The National Curriculum Guidelines for undergraduate courses in Dentistry point out the need for courses to introduce the Unified Health System (SUS) into their pedagogical projects. However, it is possible to verify gaps in teaching using the SUS as a real learning scenario, indicating the lack of instruments that assess training and internships. Thus, it is necessary to develop measurement instruments that provide objectivity to the evaluation process so that its results unfold in changes and improvements in the quality of training. Objective: To develop and validate an instrument to assess the teaching-service-community integration in undergraduate dentistry courses. Methods: This is a methodological study. The construction of the instrument took place from the theoretical foundation, with five dimensions being defined for the Teaching-Service-Community integration process: (1. Knowledge of the coordinator; 2. Planning; 3. Implementation; 4. Execution; 5. Evaluation), items and response scales. Validation using the modified Delphi Consensus took place in two rounds and a committee composed of twelve expert judges evaluated the items for clarity, objectivity, precision and relevance and whether the Likert scales adequately reflected what they were expected to measure. The Content Validity Index was used as a categorizing procedure. Suggestions regarding modifications, inclusion or elimination of items determined the items that made up the final version of the instrument. The evaluation of internal consistency used Cronbach's Alpha test. A group of 250 coordinators of undergraduate courses in dentistry were invited to participate in the research and twenty responses were obtained. The results were analyzed considering the classification of α ≥ 0.7 for Cronbach's alpha and the level of significance when p < 0.05. Results: In the first round of Delphi, 5 dimensions and 39 items were evaluated, 20 of which were validated in their original form because they reached CVI ≥ 0.8 and the others were reformulated or excluded. In Dimension 1, three items were reformulated. In Dimension 2, two were reformulated and one excluded. In Dimension 3, three items were reformulated. In Dimension 4, six items and in Dimension 5, four reformulated items and two new ones were inserted. The two Likert response scales were modified. In the second round, 20 items were evaluated, of which 18 were validated and 2 excluded. Totaling 38 validated items, as well as both scales. The internal consistency of the instrument determined using Cronbach's Alpha resulted in 0.920 viii for the 38 items, which is considered a very high level. The third dimension was excluded from the instrument because it had a negative α. Conclusions: Validations using the Delphi Consensus and Cronbach's Alpha allowed the instrument to be able to establish a relationship between the domain of the coordinator of the undergraduate course in Dentistry and the teaching-service community integration. The final instrument with four dimensions represents a proposal for evaluating training in Dentistry from a learning perspective with a view to acting in the SUS.